Entrepreneurship and institutions: A bidirectional relationship - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2017)
The interplay between entrepreneurship and institutions is crucial for economic development; however, the view that institutions determine the extent to which entrepreneurial activity is productive is only part of the story. We argue that causality is bidirectional, in that entrepreneurship is also, for better or for worse, one of the main drivers of institutional change. Through their actions, entrepreneurs have a fundamental influence on institutions, whether they abide by them, actively try to alter them, or evade them. Particular attention is given to evasive entrepreneurship, an entrepreneurial function which, until recently, has been an underappreciated and poorly understood source of innovation and institutional change. We argue that the influence of evasive entrepreneurship on the economic trajectories of societies is likely to only grow in the future.
Keywords: L5; M13; O31; P14; 330; Economic development; Entrepreneurship; Evasive entrepreneurship; Innovation; Institutional change; Regulation